The Relationship Between Resource Support, Innovation Adoption, Technology Experience, and the Use of Information Technology for Teaching by Teachers in the Secondary Education Service Area Office, Bangkok District 1 - Sopin, Kittiya; Meekun, Kosol (Journal of Buddhist Education and Research (JBER), 2025)
This research aimed to 1) study the relationship between resource support, innovation acceptance, technology experience, and teachers’ use of information technology for teaching, and 2) predict teachers’ use of information technology for teaching by resource supporting, innovation acceptance, and technology experience. This research was quantitative research. The sample consisted of 120 teachers under the Secondary Educational Service Area Office Bangkok 1, The multi-stage sampling method was used. The research instruments were summated rating scales with reliability (α) .89, The statistics used for data analysis were percentage, mean, standard deviation, Pearson’s product moment correlation coefficient, and stepwise multiple regression analysis. The research results were found as follows; 1) Resource supporting, innovation acceptance, and technology experience were moderately related to teachers' use of information technology for teaching. 2) Teachers' use of information technology for teaching could be predicted by resource supporting, innovation acceptance, and technology experience, with a percentage of prediction 26.5 when predicted the use of information technology for teaching, and a percentage of prediction 17.5 and 26 when predicted the use of scientific technology tools for teaching, and the use of new scientific methods and techniques for teaching, respectively.